Mobile technology term project - a practical application of the theory of terminology - Pietikäinen-Lahtivirta, Marja-Leena (My University, 2016)
This Design and Demonstration type of Master’s Thesis consists of two parts: it describes the practical terminology project in which I participated in my previous place of employment and it outlines the basic principles of the theory of terminology. The General Theory of Terminology was first developed to help in the practical work of categorizing and classifying concepts and this basic characteristic has prevailed. This is also visible in this Master’s Thesis: the need for collecting and organising terms in a systematic manner was the starting point of the practical terminology project. The terminology in the field of telecommunications and in the field of mobile technology started to increase as the new technology was being developed and the new products introduced. To accompany the launched products information about them was available in English and localised in several languages. The new terminology needed to be collected, harmonised, and stored for reuse in the information production, technical documentation and localisation. At the time of the project, the company employed several language specialists who were interested in terminology. Many co-operating teams and people were contacted and extensive amount of source-material and preterms were studied when the scope of the terminology corpus was planned and terms were harvested. The most active phase of the terminology project lasted for approximately 2.5 years. It was part-time work, done in addition to technical writing and localisation projects. Nevertheless, it resulted in a mobile technology terminology corpus of 200 terms and their equivalents in 24 languages collected and stored in the termbank. In addition, the entire terminology process was established and fine-tuned and the process for continuing systematic terminology work in the company was set up. Terminology work continued as a part of technical documentation and localisation work when the first part-time terminologists moved on to other projects and duties in the company. This Master’s Thesis on terminology serves not only as the introduction to the theory of terminology but also as an introduction of terminology of the particular field. It comprises a case study of practical terminology work, which is the essence of this particular master’s thesis. It also describes some of the tasks in technical documentation and terminology, at the time quite strongly growing specialist areas, on which language specialists such as translators had plenty of career opportunities.